2009
DOI: 10.1107/s0021889809041685
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of X-ray and electron backscatter diffraction textures for back-annealed Al–Mg alloys

Abstract: The potential of electron backscatter diffraction (EBSD) to determine integral macrotexture data is explored by comparing EBSD‐derived textures with standard X‐ray texture results. The comparison is performed for an Al–Mg alloy AA 5005 in the cold‐rolled and various back‐annealed states in order to analyse the impact of the microstructural state on the quality of EBSD‐based macrotextures. The number of EBSD single orientation measurements necessary to represent a texture adequately is determined by way of expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…For a grain number above 2500, J ODF can be approximated as 1 (dashed line). As demonstrated previously (Engler, 2009), a relative mean-square deviation of 10-20% from the expected ODF provides good accuracy for a subsequent texture simulation. Thus, a configuration is considered texture free if J ODF is in the range 1-1.2.…”
Section: Atomistic Modelingsupporting
confidence: 62%
“…For a grain number above 2500, J ODF can be approximated as 1 (dashed line). As demonstrated previously (Engler, 2009), a relative mean-square deviation of 10-20% from the expected ODF provides good accuracy for a subsequent texture simulation. Thus, a configuration is considered texture free if J ODF is in the range 1-1.2.…”
Section: Atomistic Modelingsupporting
confidence: 62%
“…Here, smaller trueTˆnormald values signify a more accurate texture prediction. Previous studies have suggested that trueTˆnormald values in the range of 0.1–0.2 indicate good accuracy of the texture simulation …”
Section: Visco‐plastic Self‐consistent Modelingmentioning
confidence: 98%
“…(6) where, T is the texture index [30] of the reference experimental texture ( () T values between 0.1-0.2 indicate good accuracy of the texture simulation [31,32].…”
Section: Visco-plastic Self-consistent Modellingmentioning
confidence: 99%